How Long is the Long Run? : A Dynamic Analysis of the Spanish Business Cycle - Lopez, J. (IMF Working Papers; Working Paper ;, 1997)
This paper studies the sources of Spanish business cycles. It assumes that Spanish output is affected by two types of shocks. The first one has permanent long-run effects on output and it is identified as a supply shock. The second one has only transitory effects on output and it is identified as a demand shock. Spain seems to have long business cycles, of about 15 years. As restrictive demand policies to control the inflation rate could prove painful and disappointing, supply side policies aimed at reducing rigidities in the product and labor market would be a better way to achieve the same objective.